Effect of Nitriding Temperature and Nitriding Time on MgAZ91D Alloy / Wan Amirul Shafiz Wan Zulkifli...[et al.] - Wan Zulkifli, Wan Amirul Shafiz; Mohd Rosli, Zulkifli; Mohamad Juoi, Jariah; Yusuf, Yusliza (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Magnesium and its alloys are widely applied in the automotive industries, electronic and telecommunication industries due to its low densities and excellent strength to the weight ratio. However, it possesses a low surface hardness which can weaken the adhesion properties, especially when hard coating is applied. The need of hard coating is crucial to enhance its corrosion resistance. In this work, nitriding process was carried out to modify the surface properties of MgAZ91D in enhancing its corrosion resistance. The nitriding process was conducted using a high-temperature furnace with the nitrogen gas flow at a constant rate of 5scfh. Three nitriding temperatures were set which were at 300°C, 400°C, and 500°C, for a nitriding period of 1 and 2 hours respectively. Analysis on the surface roughness of the nitrided MgAZ91D was then conducted using MitutoyoSJ410 profilometer. Surface hardness and case depth of the nitride MgAZ91D was analyzed using MitutoyoVicker's microhardness testing machine. The results showed that the surface hardness, surface roughness, grain size and the case depth of the nitrided MgAZ91D increased through the increase as the process temperature and time. However, the effect of grain size on the case depth hardness is not significant. Thus, the process temperature and time of nitriding MgAZ91D is crucial to be investigated to obtain the right combinations between the surface hardness, surface roughness and case depth for corrosion applications.